Role of DNA Methyltransferases (DNMTs) in metastasis - Qureshi, Muhammad Zahid; Sabitaliyevich, Uteuliyev Yerzhan; Rabandiyarov, Marat; Arystanbekuly, Arystanbekov Talant (Cellular and Molecular Biology, 2022)
The DNA methyltransferase (DNMT) family constitutes a conserved set of DNA-modifying enzymes which have essential functions in the modulation of epigenetics. The fundamental role of epigenetic changes in carcinogenesis and metastasis is increasingly being appreciated. DNMTs (DNMT1, DNMT3A and DNMT3B) have been shown to drive metastasis. Epigenetic machinery is installed at the target sites for the regulation of a wide variety of genes. Moreover, microRNAs, long non-coding RNAs and circular RNAs also shape the epigenetic landscape during metastasis. In this review, we have provided a snapshot of the quintessential role of DNMTs in metastasis. We also summarize how lncRNAs and circRNAs play roles in the epigenetic regulation of a myriad of genes.